If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(2x-9)=2(x-8)11
We simplify the equation to the form, which is simple to understand
-5(2x-9)=2(x-8)11
Reorder the terms in parentheses
+(-10x+45)=2*(x-8)*11
Remove unnecessary parentheses
-10x+45=+2+*(+x-8+)+*11
Reorder the terms in parentheses
-10x+45=+(+2x-16)*11
Reorder the terms in parentheses
-10x+45=+(+22x-176)
Remove unnecessary parentheses
-10x+45=+22x-176
We move all terms containing x to the left and all other terms to the right.
-10x-22x=-176-45
We simplify left and right side of the equation.
-32x=-221
We divide both sides of the equation by -32 to get x.
x=6.90625
| 20x^3+8x^2+12x= | | 4-18=z/-9 | | 12x-8=11x | | 2x^2+8x+6=8 | | 9w-8w+2=-4+2w | | 3/4c=72 | | 5j-440=30 | | 3D-10=6-5d | | -3(x-4)=-1 | | 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 | | 6-3z=-5z-8 | | g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 | | 6x+13=-5x-18 | | -9+9p=10p | | -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 | | 5-w=-16 | | 7x+10=-5x-16 | | 6x+6+2y=66 | | -5[x+6]=-5x+9 | | 12-21=-9 | | 3-6+2-1+8= | | 0.5x+3=2.5x-6 |